THORNY PROBLEMS IN THE RUBIACEAE: BENKARA, FAGERLINDIA AND OXYCEROS - C E Ridsdale (BRIN Publishing (Penerbit BRIN), 2008)
RIDSDALE,C.E.2008.Thorny problems in the Rubiaceae: Benkara,Fagerlindia and Oxyceros. Reinwardtia 12(4):289 – 298. — The shoot architecture of Fagerlindia and Oxyceros is discussed. Randia miquelii, Oxyceros rectispinaare transfered to – while Fagerlindia is reduced to a synonym of – Benkara. O. hoaensis are transferred to the genus Benkara. One new combination Oxyceros drupacea is made in the genus Oxyceros.